Environmental Concern in Nepalese Agriculture - Ghimire, Shree Ram (Journal of Agriculture and Environment, 2009)
Semi traditional to early commercial agriculture system of Nepal has now its economic move in transition from agricultural to early industrial track of economic development. An attempt has been made to assess the relationship between the emerging modern agriculture practices and environmental depletion. Some of the developmental challenges of Nepal like small land holdings, weather dependent farming systems, low per capita income, underdeveloped physical infrastructures and inefficient bureaucratic procedures are associated with comparatively higher cost of agricultural production. Natural disasters and human induced environmental degradation are closely associated with improved farming systems. Nepal has preferential ways of producing niche agricultural products by exploiting its inherent diversified climate to cope with the global open market challenges. Competitive agribusinesses along with the adoption of environmental protection measures keeping the strategy of import substitution and export promotion are the ways for sustainable agriculture development in the country. Key Words: Competitive agri-business, development infrastructures, environmental depletion, open-global market, sustainable development The Journal of Agriculture and Environment Vol:.9, Jun.2008 Page: 41-45